The Wife's Duty to Take Care of the House: A Critical Study of the Perspective of Nāṣiruddīn Al-Albānī - Arsyil Adlimi; Khairani Khairani; Boihaqi Haqi; Umi Hasheida Hussain; Uthman Mehdad Al-Turabi (al-Battar: Jurnal Pamungkas Hukum, 2026)
This article examines the wife's obligations in managing household chores from the perspective of Nasiruddin Al-Albani, highlighting the tension between classical normative constructions and the dynamics of contemporary family relations. This study uses a normative legal approach through a conceptual method, by examining Al-Albani's works as primary legal sources, supported by secondary and tertiary legal materials. The analysis is conducted in a prescriptive-critical manner to assess the relevance of this view in a modern social context. The results show that Al-Albani affirms the wife's obligation to manage domestic chores as a consequence of the marriage contract, based on the evidence of the Qur'an, hadith, and historical practices. However, when measured against contextual parameters such as changing gender roles, women's economic participation, and the principle of relational justice in the family, this view shows limited relevance. This study recommends a normative reinterpretation that emphasizes the principles of musharaka (cooperation) and ta'awun (mutual assistance) between husband and wife in managing the household.